Hubungan Anemia dan Pendapatan Keluarga dengan Kejadian Kekurangan Energi Kronis (KEK) Pada Ibu Hamil Di Wilayah Kerja Puskesmas Batu Bersurat Kabupaten Kampar Tahun 2023 - Septriani, Putry; Apriyanti, Fitri; Mayasari, Endang (Evidence Midwifery Journal, 2024)
The incidence of CED in pregnant women in Indonesia according to the results of basic health research (Riskesdas) in 2018 shows that the prevalence of CED risk in pregnant women is 17.3%. A person is said to be at risk of CED if the Upper Arm Circumference (LILA) is <23.5 cm. LILA is a way to determine the risk of chronic energy deficiency (KEK) in pregnant women. The aim of the research is to analyze the relationship between anemia and family income with the incidence of chronic energy deficiency (KEK) in pregnant women in the Batu Bersurat health center working area, Kampar Regency in 2023. Type The research is a quantitative analytical research with a cross sectional design. The research was conducted on 02-09 October 2023 with a population of 180 pregnant women and a sample of 180 pregnant women in the working area of the Batu Bersurat Community Health Center, Kampar Regency, using total sampling data collection techniques. Data collection uses a questionnaire. The data analysis used was univariate and bivariate analysis with the Chi Square test. The results of the final assignment report found that there was a relationship between anemia and the incidence of CED in pregnant women in the working area of the Batu Bersurat Community Health Center, Kampar Regency in 2023 (p value = 0.002) and there was no relationship between income and the incidence of CED in pregnant women in the working area of the Batu Bersurat Regency Community Health Center. Kampar in 2023 (p value = 0.784). It is hoped that Batu Bersurat Community Health Center officers will need to provide nutritional education about CED and how to prevent CED in pregnant women.